Pentraxin 3 levels and correlation with disease severity in patients with acute rheumatic fever - Dolunay GÜRSES; Merve OĞUZ; Münevver YILMAZ; Hülya AYBEK; Funda AKPINAR (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate serum pentraxin 3 (PTX3) levels during acute episode of acute rheumatic fever (ARF) and their relationship with disease severity. Patients and methods: The prospective study was conducted between January 2015 and December 2018 and included 52 ARF patients (22 girls, 30 boys, mean age 10.7±2.1 years; range, 5 to 16 years) experiencing an acute episode and 22 healthy children (13 girls, 9 boys, mean age 10.3±3.8 years; range, 5 to 16 years). ARF patients were classified into three groups based on the clinical course: isolated arthritis (n=17), mild carditis (n=19), and moderate/severe carditis (n=16). Blood samples were collected from all patients before treatment and from the healthy children in the control group to measure PTX3 levels. PTX3 was measured using sandwich enzyme-linked immunosorbent assay method. Results: Plasma PTX3 levels were significantly higher in ARF group compared to the control group (4.7±5.2 and 1.2±1.7 ng/mL, p<0.001). Subgroup analysis of serum PTX3 levels in ARF patients with isolated arthritis, mild carditis, and moderate/severe carditis (3.2±3.1 ng/mL, 4.3±5 ng/mL, and 6.7±6.6 ng/mL, respectively) showed that serum PTX3 was significantly higher in the moderate/severe carditis group compared to the other groups (p<0.05). Analysis of echocardiographic data showed that serum PTX3 was positively correlated with left ventricular end-diastolic diameter, left atrial diameters, and mitral A velocity and negatively correlated with E/A ratio (p<0.05; r=0.231, 0.402, 0.562, -0.586, respectively). Conclusion: High PTX3 level during an acute episode of ARF may help predict the clinical course and the severity of accompanying carditis. However, prospective studies with larger sample sizes are needed.